A Peek at Prehistoric Paisley: Early Bronze Age Evidence from Wellmeadow Street. Issue 1 (March 2023) - Lowther, Jessica
Abstract : Minor archaeological works completed at Wellmeadow Street, Paisley between 2017 and 2018 have identified evidence of prehistoric activity in the centre of the city. Comprising a single prehistoric feature and a shafthole stone, the finds from these works demonstrate the importance of archaeological mitigation, even in areas of low expectation.